The Seattle Central District (Cd) Over Eighty Years. Issue 3 (26th August 2013) - Morrill, Richard
Abstract: The evolution of Seattle's "Central Area" or "CD" is traced for eighty years from 1930 through 2010. Relevant theory about social and economic discrimination and urban development is presented first. This is followed by a brief history of the Central Area as a black community and a review of relevant literature. The changing distribution of the Central Area is presented through a series of maps, from an unexpected origin and development in a relatively desirable area east of downtown Seattle to its gradual displacement far southward, as central Seattle experienced gentrification. This spatial change is evaluated with respect to the expectations from theory presented earlier.